Experimental Assessment of a Back-To-Back Modular Multilevel Converter for Hvdc Applications - Espina-Gonzalez, E; Diaz-Diaz, M; Ibaceta-Valenzuela, E; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2023)
The Modular Multilevel Converter is a topology employed and studied in HVDC transmission scenarios to manage incremental demand in offshore and onshore wind plants due to its profits, such as scalability, modularity, and power density in HVDC systems that couple two high-power systems. As early publications, despite its industrial popularity, the MMC validated in test benches in laboratory scenarios considered a lack of experimental results for being composed of at most 60 cells and even more for HVDC applications. Therefore, this paper presents the employment of dedicated cabinets to permit the experimental testing of an HVDC system composed of two MMC and operating with a Back-to-Back configuration, enabling a power flow between AC ports. © 2023 IEEE.